MODEL PENILAIAN HISTORIS-KRITIS BERBASIS PARADIGMA KONSTRUKTIVISTIK DALAM PEMBELAJARAN SEJARAH: SEBUAH KAJIAN KONSEPTUAL - Heri Agung Ramdani; Damanik , Juan Andrian; Br Sembiring , Quia Natasya; Simarmata, Dea Anastasya; Sihombing , Bonar; Br Tarigan , Riana Debora; Sitorus, Enjelika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
History learning carries a strategic mission in shaping students' historical consciousness, critical thinking, and national identity. However, assessment practices in schools are still predominantly dominated by fact-memorization approaches dates, figures, events which fail to comprehensively measure historical thinking competencies. This article aims to design the Historical-Critical Assessment Model (HCAM) as an alternative history learning assessment grounded in the constructivist paradigm. The method employed is a conceptual review based on library research, identifying problems in history assessment, reviewing theories of evaluation, constructivism, authentic assessment, and historical thinking, then synthesizing them into a cohesive model design. HCAM consists of five main components: historical source analysis, understanding of chronology and context, comparison of historical perspectives, construction of evidence-based arguments, and reflection on values and contemporary relevance. The model is equipped with six implementation steps and an authentic assessment rubric on a 1–4 scale. The novelty of this article lies in the explicit integration of three pillars that have not been previously unified in a single history assessment design: the constructivist paradigm, historical thinking framework, and authentic assessment principles. Theoretically, HCAM enriches the discourse on history learning evaluation; practically, it can be adapted in the Merdeka Curriculum implementation that emphasizes meaningful learning and the development of the Pancasila Student Profile.